Legal Deconstruction of Ecotourism-Based Cultural Tourism Management in Creative Economic Development in Badung-Bali District - I Wayan Wesna Astara; NP Budiartha; Putu Ayu Sriasih Wesna (Journal of Legal and Cultural Analytics, 2023)
The tourism political journey in Bali continues to develop Balinese cultural tourism, the philosophy of Tri Hita Karana, and Balinese culture, traditions, and customs according to Balinese religious and cultural norms. In the Regional Regulation of the Province of Bali Number 5 of 2020, regarding Balinese cultural tourism standards, the author deconstructs laws related to mass tourism versus ecotourism. For this reason, the purpose of this research is to find out the legal arrangements for the concept of ecotourism-based cultural tourism in Bali and the implementation of the concept of cultural tourism in Bali in managing ecotourism in each traditional village. The results of the research on the legal deconstruction of cultural tourism practices in Bali and ecotourism in Subak Umalambing, Subak Mambal, and Pandawa Beach Kutuh-Kuta Utara are processed based on "legal behavior" from below, not based on "state legal texts" but instead based on Balinese customary law based on Pararem.